THE EFFECT OF MARKETING ASSET ACCOUNTABILITY ON MARKETING PERFORMANCE AND STRATEGY: A NATURAL EXPERIMENT TO TEST ITS IMPACT IN A BUSINESS CONTEXT - Aripin, Zaenal; Paramarta, Vip; Kosasih (Yayasan Kreatif Indonesia Emas, 2024)
This research aims to investigate the effect of marketing asset accountability on company financial performance and marketing strategy, using a natural experiment method. A total of 250 companies from three different industrial sectors (technology, finance, food/beverage) were research subjects. Correlation analysis shows that variables such as measuring the success of advertising campaigns, real-time tracking systems, and accountability cost efficiency of marketing assets are positively correlated with company revenue, net profit, and return on capital. In addition, differences in marketing asset accountability practices between industry sectors highlight the need for approaches tailored to the characteristics of each sector. A natural experiment was conducted to evaluate the impact of increasing marketing asset accountability on marketing strategy performance. Experimental results show that implementing a real-time tracking system and increasing cost efficiency makes a positive contribution to customer conversion, return on investment and effectiveness of advertising campaigns. These findings provide practical insights for companies in better managing their marketing assets. In conclusion, this research reinforces the importance of marketing asset accountability in achieving optimal financial performance and successful marketing strategy formulation. The practical implication is that companies need to focus on careful measurement, efficient tracking technology, and wise cost management to increase the accountability of their marketing assets, taking into account the specific context of the industry sector.